Ovariectomy exacerbates the disturbance of excitation- inhibition balance in the brain of APP/PS-1/tau mice - Liu, Fuwang; Liu, Yanman; Shen, Xuri; Du, Jiarui; Zhang, Hanting; Hou, Xueqin (Frontiers in Molecular Neuroscience, 2024)
IntroductionThe prevalence of Alzheimer’s disease (AD) is significantly gender-differentiated, with the number of female AD patients far exceeding that of males, accounting for two-thirds of the total prevalence. Although postmenopausal AD mice have been shown to have more prominent pathologic features and memory impairments than normal AD mice, the relevant molecular mechanisms leading to these outcomes have not been well elucidated. In the present study, we used the disturbance of excitation-inhibition balance in the postmenopausal brain as an entry point to explore the link between estrogen deficiency, disorders of the glutamatergic-GABAergic nervous system, and memory impairment.MethodsWild-type (WT) mice and APP/PS1/tau (3 × Tg-AD) mice (10 months old) were randomly divided into four groups: WT+Sham group, WT+OVX group, 3 × Tg-AD+Sham group and 3 × Tg-AD+OVX group. Ovariectomy (OVX) was performed in the WT+OVX group and the 3 × Tg-AD+OVX group, and sham surgery was performed in the WT+Sham group and the 3 × Tg-AD+Sham group. The learning and memory ability and the anxiety and depression-like behavior changes of mice were evaluated by behavioral experiments, and the association between estrogen-estrogen receptors pathway and glutamatergic/GABAergic nervous system and female AD was evaluated by neurochemical experiments.ResultsIn WT and 3 × Tg-AD mice, OVX resulted in impaired learning and memory abilities and anxiety and depression-like behaviors; reduced estrogen levels and downregulated the expression of estrogen receptors; upregulated the expression of amyloid-β, amyloid precursor protein, presenilin 1, and p-tau; upregulated the expression of Bcl-2-associated X protein and downregulated the expression of B-cell lymphoma-2, promoting cell apoptosis; reduced the number of neuronal dendrites and downregulated the expression of postsynaptic density protein-95; more importantly, OVX increased brain glutamate levels but downregulated the expression of N-methyl-D-aspartate receptor-2B, excitatory amino acid transporter 1, excitatory amino acid transporter 2, γ-aminobutyric acid receptor-A and γ-aminobutyric acid receptor-B.ConclusionOur results suggested that OVX-induced estrogen-estrogen receptors pathway disruption caused learning and memory impairment and anxiety and depression-like behaviors, upregulated the expression of AD pathological markers, promoted apoptosis, destroyed neuronal structure, and most importantly, caused glutamatergic/GABAergic nervous system disorders.